Studi Fenomenologi Pengelolaan Keuangan UMKM melalui Sistem Budgeting Berbasis Filantropi Islam - Haerani Dewi Ayu; Itsni Tsamrotul Hasanah; Mohammad Daviq Johari; Najwa Aqila Almutawali; Suhendi Suhendi (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines how Islamic philanthropy-based budgeting practices contribute to strengthening the financial resilience of Micro, Small, and Medium Enterprises (MSMEs). Many MSMEs continue to face financial instability due to weak budgeting practices, limited emergency funds, and dependence on external financing. This research aims to explore the lived experiences of MSME actors in integrating Islamic philanthropic values into their financial planning and daily budgeting activities. The study employed a qualitative phenomenological approach involving eight MSME owners selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation of financial records, then analyzed using the Miles and Huberman interactive model. The findings indicate that allocating funds for zakat, infaq, and sadaqah in a structured manner encourages greater financial discipline, reduces impulsive spending behavior, and strengthens social support networks during financial difficulties. Participants also perceived philanthropic budgeting as a form of moral responsibility that promotes long-term financial stability. The integration of spiritual values into budgeting practices was found to support adaptive financial behavior and improve the resilience of MSMEs in dealing with economic uncertainty.